MANAJEMEN PERGURUAN TINGGI MENUJU PERUBAHAN KUALITAS LAYANAN MUTU - Hakim, Lukman (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Abstract: This article is aimed at discussing the management of college tat has to be improved and changed as a means of giving high quality of service to users. Currently the college can not stand idly by and as organization it must move forward, dynamic and positive impact on the organization development. Regional challenges and dynamic as symmetrical problem of national and global and must be answered by the college. The position of Indonesia below Thailand, Malaysia, Singapore in quality should be a trigger to improve the quality of the qualified graduates. Need for evaluation and re-formulation of the vision, mission, organizational goals through programs that have been created to make the right strategy in order to accelerate the quality of better quality. So that a college can address community needs and can respond to changing global society.Keywords: Management, quality, college